ANALYSIS OF FACTORS INFLUENCING MCDONALD'S CONSUMER PURCHASE DECISION IN JAKARTA - Fortuna, Clarissa; Firdausy, Carunia Mulya (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to analyze factors affecting the purchase decision of consumers on McDonald's fast-food restaurant in Jakarta. The sample selection method used the non-probability sampling method with a convenience sampling technique. The number of samples collected was 120 respondents. Method to collect the data was by using questionnaire and this data was analyzed by employing multiple regression analysis. The results show the quality of product and price have no significant effects on purchasing decisions of McDonalds’consumers in Jakarta. While promotion, location and brand image have significant influence on purchasing decision of McDonalds’consumers in Jakarta. The implication of the results of this research is that McDonalds needs to keep improving the promotion, location, and brand image to improve consumers’ purchase decision in a better shape.